Kerangka Konseptual Transformasi Digital untuk Efisiensi Operasional FMCG: Studi Literatur Sistematis - Wardani, Puja; Dirgahayu, Teduh (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
This study aims to identify challenges, mitigate strategies, and develop an operational efficiency framework for fast-moving consumer goods (FMCG) industry. Using a systematic literature review (SLR) with PRISMA rules, 14 articles (2023-2025) were obtained, which were then analyzed using the Hexagon socio-technical system (STS) model. The analysis revealed social challenges such as competency gaps and cultural resistance, as well as technical challenges such as infrastructure limitations and data security issues. Mitigation strategies include digital competency training, the implementation of an enterprise architecture framework, and the adoption of hybrid infrastructure. This study proposes a joint optimization-based framework that aligns organizational readiness, technical execution, and balances the two toward operational efficiency. It is recommended that inclusive change management, investment in flexible infrastructure, and alignment of technology roadmaps with strategic company performance indicators be implemented.